Pengaruh Intensitas Penggunaan Game Online Terhadap Disiplin Belajar Siswa SMA Negeri 2 Palangka Raya - Febry Ortega Rita Tampubolon; Romiaty Romiaty (FKIP Universitas Palangka Raya, 2023)
This study aims to determine how much influence the intensity of using online games has on the learning discipline of SMA Negeri 2 Palangka Raya students. The research method used is a quantitative method, where in quantitative research the main instruments are the results of interviews, observations and questionnaires. In this study the data collection techniques used were interviews, observations, and questionnaires. This research was conducted at SMA Negeri 2 Palangka Raya, October 2022 – November 2022. In this study, data analysis techniques were used for normality tests, homogeneity tests and simple correlation analysis. The results of this study indicate that the intensity of using online games contributes to the learning discipline of class XII IPS students at SMA Negeri 2 Palangka Raya by 39%. It can be concluded that the learning discipline of class XII IPS students at SMA Negeri Palangka Raya is influenced by the intensity of using online games by 39%, while 61% is determined by internal and external factors which include the physical and environmental conditions of students.